Effect of cataract extraction on the pupil response to mydriatics. Issue 7 (July 1989) - Gibbens, M V; Goel, R; Smith, S E
Abstract : Pupil diameters in the dark, in the light, and after mydriasis with tropicamide+ phenylephrine have been measured in 25 patients before and six months after cataract surgery. The aphakic pupil showed reduced mobility as evidenced by a smaller diameter in the and a larger one in the light. In patients who had intracapsular extraction or extracapsular extraction with intraocular lens implantation the pupils dilated less well than preoperatively. The difference in response to mydriatics is of practical importance in the assessment and treatment of peripheral retinal disorders in aphakic and pseudophakic eyes.